Minimally Invasive Implantation of Biventricular Assist Devices - Deuse, Tobias; Reichenspurner, Hermann (The Thoracic and Cardiovascular Surgeon, 2014)
As minimally invasive left ventricular assist device implantation is being advocated and more widely performed, bailout strategies for postoperative right ventricular failure (RVF) become necessary. We describe our surgical technique for additional right ventricular assist device implantation through a third mini-thoracotomy incision. This new technique allows avoidance of sternotomy even if RVF occurs.
Keywords: circulatory assist devices; minimally invasive surgery; heart failure